IN SILICO, PREPARATION AND IN VITRO STUDIES OF BENZYLIDENE-BASED HYDROXY BENZYL UREA DERIVATIVES AS FREE RADICAL SCAVENGERS IN PARKINSON’S DISEASE - CHAND, JAGDISH; KANDY, AMARJITH THIYYAR; PRASAD, KAVERI; MATHEW, JINU; SHERIN, FARHATH; SUBRAMANIAN, GOMATHY (International Journal of Applied Pharmaceutics, 2024)
Objective: The study focuses on the benzylidene-based hydroxy benzyl urea derivative as free radical scavengers in PD. Methods: The derivatives were designed, synthesized, and characterized using FTIR, 1H, 13C-NMR, and Mass spectrometry. Further in vitro studies were performed on the SHSY-5Y cell lines. Molecular docking and molecular dynamic studies were performed at 100 ns to predict the binding affinity and stability of the ligand/protein complex. Results: Among the nine derivatives, compounds HBU-2, and HBU-4were found to have the highest binding affinity-9.699 kcal/mol, and-9.020 kcal/mol with the amino acid interactions SER 149, PHE 157, ARG 158, SER 159, ILE 230, and ASP 231. Further, this HBU-1 to HBU-9 derivatives were produced using a synthesis route. The neurotoxicity studies were performed on the SHSY-5Y cells, where the % cell viability for the compound HBU-2, and HBU-4 was 91.22 %, and 90.42 %at a minimal concentration of 125 µg/ml with a p-value<0.011. Further, the cell counts and LDH assay for the compound HBU-2, and HBU-4 with MPP+treatment predicted 0.72-fold change and 0.66-fold change. The ROS % activity was also measured for compounds HBU-2 and HBU-4 in conjunction with the MPP+induction. In the SHSY-5Y cell line, compound HBU-2 downregulated the ROS level to 45%. Conclusion: The synthesized compounds were found to have good free radical scavenging properties on SHSY-5Y neuroblastoma cell lines, considering these derivatives could be further assessed using appropriate PD models.